'It's a man's man's man's world': Music groupies and the othering of women in the world of rock. (May 2017) - Larsen, Gretchen
Groupies are understood as a particular type of fan that are most commonly associated with rock music. The 'groupie' identity is almost exclusively applied to female fans but sometimes also to female music producers and is largely used in a derogatory manner both by the popular media and by fans themselves. This article argues that the 'groupie' identity is used to 'other' and exclude women from creative production in rock music. This study draws on a rhetorical analysis of five published biographical accounts of groupies to examine how the labeling of certain people as 'groupies' works as an othering practice that serves to support and maintain the gendered norms of rock and identifies three underlying discursive processes. First, popular and music media played a significant role in stereotyping groupie as female right from the emergence of the label. Second, the notions of 'credibility' and 'authenticity', which are central to serious music journalism, are constructed in such a way as to stigmatize and therefore exclude women from rock, primarily by reframing 'groupies' as inauthentic consumers rather than proper fans. Finally, the intertwining of femininity with fandom, as occurs in groupiedom, serves to magnify cultural assumptions about women as sex objects and as passive consumers of mass culture. In elucidating both the gender and marketplace role politics at play in the 'groupie' identity and the mechanisms involved in othering women, space is opened in which alternative possibilities for understanding and enacting the role of women in rock can be imagined.